Effect of exercise and antioxidant supplementation on cellular lipid peroxidation in elderly individuals: Systematic review and network meta-analysis - Ni, Chunxia; Ji, Yiyi; Hu, Keke; Xing, Kai; Xu, Yining; Gao, Yanan (Frontiers in Physiology, 2023)
Background: The viewpoints of previous studies on the correlation between exercise and cellular lipid peroxidation are contradictory from many perspectives and lack evidence for elder individuals. A new systematic review with network meta-analysis is necessary and will have significant practical value to provide high-quality evidence in the development of exercise protocols and an evidence-based guide for antioxidant supplementation for the elderly. Aims: To identify the cellular lipid peroxidation induced by different types of exercise, with or without antioxidant supplementation, in elderly individuals. Methods: Randomized controlled trials that recruited elderly participants and reported cellular lipid peroxidation indicators and were published in peer-reviewed journals in English were searched by a Boolean logic search strategy and screened in the databases PubMed, Medline, Embase, and Web of Science. The outcome measures were the biomarkers of oxidative stress in cell lipids in urine and blood, namely F2-isoprostanes, hydrogen peroxide (LOOH, PEROX, or LIPOX), malondialdehyde (MDA), and thiobarbituric acid reactive substances (TBARS). Result: 7 trials were included. A combination program of aerobic exercise (AE), low-intensity resistance training (LIRT), and a placebo intake (Placebo) and a combination program of aerobic exercise, low-intensity resistance training, and antioxidant supplementation (S) had the most and sub-most potential to dampen cellular lipid peroxidation (AE+LIRT+Placebo: 0.31 in Rank 1 and 0.2 in Rank 2; AE+LIRT+S: 0.19 in Rank 1 and 0.20 in Rank 2); A placebo intake (Placebo) and a blank intervention without exercise (NE) had the most and sub-most potential to induce an enhancement of cellular lipid peroxidation (Placebo: 0.51 in Rank 9 and 0.16 in Rank 8; NE: 0.16 in Rank 9 and 0.28 in Rank 8). All included studies had an unclear risk of selecting reporting. There were no high confidence ratings in all the direct and indirect comparisons, 4 comparisons in the direct evidence structure and 7 comparisons in the indirect evidence structure had moderate confidence. Conclusion: A combined protocol consisting of aerobic exercise and low-intensity resistance training is recommended to dampen cellular lipid peroxidation. Extra antioxidant supplementation might be unnecessary if an elderly individual has enough aerobic and resistance exercise. Registration Number: CRD42022367430.